Dynamic equalization and fast settling based wide operating voltage range 93 ​dB PSRR PTAT current reference. (July 2020) - Jing, Kai; Yu, Ningmei; Quan, Xing; Yang, Zhaonian; Guo, Zhongjie
Abstract: This paper presents a novel PTAT current reference with fast settling behavior and high PSRR in UMC 110 ​nm technology. In addition to a classic voltage-clamp operational amplifier for forming △VBE /R, a novel extra operational amplifier with functions of current dynamic equalization and automatic active fast start-up and shut-off is introduced to enhance the settling behavior and current matching accuracy. Results have shown that more than 93 ​dB PSRR across the temperature range of -40—85 ​°C is achieved. The complete design consumes a total current of 22.03 μA from a 2.5 ​V power supply with only 20% in auxiliary circuits, and correct and seamless transition from off state to steady state is realized.